Emma Dabiri, What White People Can Do Next: From Allyship to Coalition. London: Penguin, 2021. 157 pp. - Alonso-Breto, Isabel (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2023)
Review of Emma Dabiri, What White People Can Do Next: From Allyship to Coalition. London: Penguin, 2021. 176 pp. ISBN: 9780063112711.